Design and synthesis of novel oridonin analogues as potent anticancer agents - Qing-Kun Shen; Zheng-Ai Chen; Hong-Jian Zhang; Jia-Li Li; Chuan-Feng Liu; Guo-Hua Gong; Zhe-Shan Quan (Taylor & Francis Group, 2018)
To identify anticancer agents with higher potency and lower toxicity, a series of oridonin derivatives with substituted benzene moieties at the C17 position were designed, synthesised, and evaluated for their antiproliferative properties. Most of the derivatives exhibited antiproliferative effects against AGS, MGC803, Bel7402, HCT116, A549, and HeLa cells. Compound 2p (IC50 = 1.05 µM) exhibited the most potent antiproliferative activity against HCT116 cells; it was more potent than oridonin (IC50 = 6.84 µM) and 5-fluorouracil (5-FU) (IC50 = 24.80 µM). The IC50 value of 2p in L02 cells was 6.5-fold higher than that in HCT116 cells. Overall, it exhibited better selective antiproliferative activity and specificity than oridonin and 5-FU. Furthermore, compound 2p arrested HCT116 cells at the G2 phase of the cell cycle and increased the percentage of apoptotic cells to a greater extent than oridonin.